Contemporary management of genitourinary injuries in a tertiary trauma centre in Nigeria - Ofoha, Chimaobi G.; Shu’aibu, Samaila I.; Onowa, Victor E.; Galam, Zingkur Z. (International Journal of Research in Medical Sciences, 2018)
Background: The genitourinary system has been shown to be involved in 10% of patients presenting after trauma and is therefore a significant factor in trauma induced morbidity and mortality. It affects all age groups and both sexes. The aim of this study is to determine the aetiology, mechanism of injury and management of genitourinary injuries in a tertiary trauma centre. Methods: This is a prospective study carried out at the Jos University Teaching Hospital between 2012 and 2017. All patients who presented at the A and E with genitourinary trauma were recruited into the study. Initial assessment involved taking an AMPLE history and resuscitation, using the Advanced Trauma Life Support (ATLS) protocol of the American College of Surgeons. Physical examination and investigation were carried out to localize and determine extent of injury. Investigations carried out were complete blood count, blood grouping, serum electrolyte, urea and creatinine and radiography where applicable. Surgical intervention was carried out where indicated. Results: A total of 104 patients were involved in this study. The mean age was 32.14±15.5 years with a range of 3 to 75yrs. Median age was 28yrs. Eighty-nine (85.6%) were males while fifteen (14.4%) were females. The genitalia were the most affected in 34% (n=35) of the patients. Gunshot was the commonest mechanism of injury (37.5%, n=39). Operative and non-operative management were employed depending on mechanism and extent of injury. Conclusions: Gunshot was the commonest cause of genitourinary trauma. These injuries require specialized attention for proper assessment and management.